Reaktualisasi Moralitas Profetik di Era Digital: Analisis Etis Berdasarkan Hadits Tentang Akhlak Dalam Islam - Panjaitan, Lutpiah Sapitri (INKLUSIF: Jurnal Pendidikan Islam, 2026)
The rapid growth of digital technology has reshaped social interaction while generating serious ethical challenges, including hate speech, misinformation, privacy violations, and moral polarization. These phenomena indicate a crisis of digital morality marked by weakened character formation. Although digital ethics has developed various normative frameworks, it remains largely dominated by secular and technocratic perspectives, with limited engagement with religious moral traditions. This study examines prophetic morality derived from hadith on aqidah and akhlaq as a virtue-based ethical framework for addressing moral challenges in digital environments. This research employs a qualitative library research method by analyzing classical hadith texts, their commentaries, and contemporary literature on Islamic ethics and digital ethics. The data were analyzed thematically and interpretatively to identify core moral values and assess their relevance in the digital context. The findings reveal that prophetic morality emphasizes key virtues such as honesty (ṣidq), trustworthiness (amanah), social responsibility, communicative etiquette (adab al-kalām), self-restraint, and moderation (wasatiyyah). These values align with virtue ethics and offer a normative foundation for ethical digital behavior. The study concludes that prophetic morality can serve as a virtue-based digital ethics framework that complements existing rule-based approaches by prioritizing character formation. Perkembangan teknologi digital telah mengubah pola interaksi sosial sekaligus melahirkan berbagai tantangan etis, seperti ujaran kebencian, disinformasi, pelanggaran privasi, dan polarisasi moral. Fenomena tersebut menunjukkan adanya krisis moral digital yang ditandai oleh melemahnya pembentukan karakter. Meskipun kajian etika digital telah berkembang, diskursusnya masih didominasi oleh perspektif sekuler dan teknokratis, sementara tradisi moral keagamaan belum banyak diintegrasikan. Penelitian ini mengkaji moralitas profetik yang bersumber dari hadis aqidah akhlak sebagai kerangka etika berbasis kebajikan untuk merespons tantangan moral di ruang digital. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan melalui analisis hadis, syarah hadis, serta literatur kontemporer tentang etika Islam dan etika digital. Data dianalisis secara tematik dan interpretatif. Hasil penelitian menunjukkan bahwa moralitas profetik menekankan nilai-nilai kebajikan utama seperti kejujuran (ṣidq), amanah, tanggung jawab sosial, kesantunan berkomunikasi, pengendalian diri, dan moderasi (wasatiyyah). Nilai-nilai tersebut sejalan dengan pendekatan virtue ethics dan dapat menjadi fondasi etika bermedia digital yang berorientasi pada pembentukan karakter moral.